Evaluation of nutritional status and prognostic impact assessed by the prognostic nutritional index in children with chronic kidney disease - Hui Zhang; Yuhong Tao; Zheng Wang; Jing Lu (2019)
Abstract To evaluate the nutritional status of children with chronic kidney disease (CKD) before dialysis via a series of indexes, and investigate the prognostic impact of nutritional status in these patients assessed by the Prognostic Nutritional Index (PNI). Fifty-four children with CKD before dialysis were enrolled in this study. The nutritional status was evaluated by different indexes, including dietary intake, anthropometry data and biochemical parameters. Additionally, PNI is calculated as 10 × serum albumin (g/dL) + 0.005 × lymphocyte count (/mm 3 ). Glomerular filtration rate (GFR) of patients with different PNI scores was followed up. Thirty-four patients (63.0%) experienced unreasonable dietary intake, and the patients with CKD stage 4 were characterized by lower energy intake. The height was the most affected anthropometry parameter. Additionally, 46 patients (85.2%) suffered from anemia. The serum albumin of 42 patients (77.8%) was <35 g/L, while 34 cases (63.0%) had increased cholesterol and triglyceride. According to the PNI scores, the patients were divided into 3 groups: high-PNI (PNI ≥ 38), middle-PNI (35 ≤ PNI < 38), and low-PNI (PNI < 35). Of the 54 patients, the PNI was <35 in 29 (53.7%) and ≥38 in 13 (24.1%). The patients with CKD stage 4 were belonged to the low-PNI group. At follow-up, GFR decreased significantly in patients with low-PNI scores compared with the high-PNI group ( P < .05). Malnutrition, as a common complication of CKD, has a prognostic impact in children with CKD before dialysis, as assessed by the PNI score.